Cardiometabolic effects of contrast therapy: A systematic review - Veerle de Haan; Guy Plasqui; Hannah Pallubinsky (Experimental Physiology, 2026)
Abstract The rising prevalence of overweight and obesity, together with associated cardiometabolic disorders, underscores the need for additional strategies alongside established interventions. The growing popularity of contrast therapy – alternating exposure to heat and cold, a practice common in traditional Finnish sauna bathing – has prompted interest in its potential cardiovascular and metabolic health benefits. This systematic review outlines the acute and chronic effects of contrast therapy on cardiometabolic outcomes. The review followed PRISMA guidelines and searched three databases (PubMed, Scopus, Web of Science) until 17 June 2025. Interventional studies reporting cardiovascular and/or metabolic outcomes were included; 21 studies were identified, of which 19 contributed to data synthesis. Continuous outcomes were converted to standardised mean differences to enable comparison. Little evidence for effects of contrast therapy was found on resting heart rate, blood pressure or vascular health, all indicators of cardiovascular risk, and metabolic outcomes, including glucose and lipid metabolism. Some evidence of heat adaptation was observed, indicated by attenuated acute heart rate and core temperature responses, and decreased resting core temperature upon contrasting thermal exposure. However, the evidence base is limited, restricting the ability to draw firm conclusions or provide clear recommendations. Well‐designed, controlled studies, with systematic assessment of vascular and metabolic outcomes, are needed to further clarify the acute and long‐term effects of contrast therapy on cardiometabolic health.